Mid-Term Patency in Radial Artery and Saphenous Vein After Coronary Artery Bypass Grafting in Asymptomatic Patients Using 128-Slice CT Coronary Angiography - Sadeghpour, Ali (Anesth Pain Med, 2015)
BACKGROUND: Patency of the revascularization conduit is an essential predictor of long-standing survival after coronary artery bypass grafting. OBJECTIVES: We have conducted this study to compare the mid-term patency rates of radial artery (RA), left internal thoracic artery (LITA) and also saphenous vein (SV) grafts in asymptomatic patients following coronary artery bypass graft surgery (CABG) undergoing total IV anesthesia. PATIENTS AND METHODS: In this study, 30 three-vessel disease patients with 104 RA, LITA, and SV grafts used concomitantly for primary isolated non-emergent CABG surgery were assessed. The primary end point was CT angiographic graft patency rate. After 53.5 (24-97) months’ follow-up, graft patency was assessed using 128-slice CT coronary angiography. Logistic regression analysis was used to detect the independent predictors of graft failure. RESULTS: A total of 104 grafts, including 30 LITA, 44 SV, and 30 RA grafts, were studied. Cumulative graft patency rates were 93.3% in LITA, 83.3% in RA, and 70.5% in SV grafts. Statistically significant difference was found between the LITA and the SV graft patency rates (P = 0.019), whereas the difference between the RA conduit patency and the LITA or SV graft patency rates did not have any statistical significance (P = 0.424 and P = 0.273, respectively). Independent predictors of RA grafts occlusion were native coronary stenosis < 70% and female gender. CONCLUSIONS: In our patients, the RA grafts had an acceptable patency rate in 2 to 5 years’ follow-up. Although the SV grafts had a relatively higher patency rate than RA grafts in our asymptomatic patients, the patency rates in RA and SV grafts were close to each other. The RA graft function was poor in the patients with a higher number of risk factors and in the females.